1990
DOI: 10.1021/ja00171a020
|View full text |Cite
|
Sign up to set email alerts
|

A zinc(II) complex of 1,5,9-triazacyclododecane ([12]aneN3) as a model for carbonic anhydrase

Abstract: Among macrocyclic triand tetraamines tested, a 12-membered triamine, [12]aneN3, is the most appropriate ligand that mimics the ligand field surrounding Zn" in carbonic anhydrases. In its 1:1 ZnnL complex, the H20 bound at the fourth coordination site deprotonates with the pK, value of 7.30 at 25 °C, / = 0.1 (NaC104), almost the same value being reported for the Zn"-enzymes. The resulting hydroxo complex is precipitated as a trimer from pH 8 aqueous solution, which with a formula of [ZnIIL(0H)]3(C104)3'HC104 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
209
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(229 citation statements)
references
References 0 publications
15
209
0
5
Order By: Relevance
“…331,335,350,351 The investigators measured potentio-metrically the value of pK a to be 7.3 for the Zn-bound water in this complex; this value is very close to that found in CA II (~6.9 for BCA II, 6.8 for HCA II). 331 Using either the tri(amine) or tetra(amine) macrocyclic scaffold, the investigators could vary the number of nitrogen ligands to Zn II from 3 to 4 and, thus, were able to demonstrate that increasing the coordination state of Zn II increased the value of pK a of Zn II -OH 2 + . Thus, they were able to show that the value of pK a of the Zn II -OH 2 + group in the native protein is mainly determined by the coordination number of Zn II , rather than by the hydrophobic environment in the binding pocket.…”
Section: Physical-organic Models Of the Active Site Of Casupporting
confidence: 69%
See 1 more Smart Citation
“…331,335,350,351 The investigators measured potentio-metrically the value of pK a to be 7.3 for the Zn-bound water in this complex; this value is very close to that found in CA II (~6.9 for BCA II, 6.8 for HCA II). 331 Using either the tri(amine) or tetra(amine) macrocyclic scaffold, the investigators could vary the number of nitrogen ligands to Zn II from 3 to 4 and, thus, were able to demonstrate that increasing the coordination state of Zn II increased the value of pK a of Zn II -OH 2 + . Thus, they were able to show that the value of pK a of the Zn II -OH 2 + group in the native protein is mainly determined by the coordination number of Zn II , rather than by the hydrophobic environment in the binding pocket.…”
Section: Physical-organic Models Of the Active Site Of Casupporting
confidence: 69%
“…Thus, they were able to show that the value of pK a of the Zn II -OH 2 + group in the native protein is mainly determined by the coordination number of Zn II , rather than by the hydrophobic environment in the binding pocket. 331 Kimura et al also demonstrated that [12]aneN 3 , like CA, was able to catalyze the hydration of acetylaldehyde and hydrolysis of methyl acetate or p-nitrophenyl acetate, albeit with second-order rate constant 1 order of magnitude lower than those of BCA II. The pH profile of the rate of these reactions showed an inflection point near pH = 7.3, agreeing with potentiometric measurements for the value of pK a and indicating that the reaction mechanism involves a nucleophilic attack by Zn II -OH.…”
Section: Physical-organic Models Of the Active Site Of Camentioning
confidence: 99%
“…252,270 The pK a values reported for Zn(II)-bound water molecules in a range of model complexes depend strongly on the coordination environment and range from 7.3 to 10.8. [290][291][292][293][294][295][296] Since E. coli 5′-NT is an efficient catalyst even at pH 6, it seems likely that the pK a of the terminal water molecule is lowered through hydrogen bonding interactions with His117 ( Figure 22A). The pH dependence of kinetic parameters for 5′-NT-catalyzed reactions has not yet been analyzed in detail, but based on pH optima ranging from 5.5 to 9 for different enzymes, it appears that in some 5′-NTs the likely candidate for the role of a nucleophile is the bridging water ligand, which is expected to have a lower pK a value.…”
Section: Catalytic Mechanismmentioning
confidence: 99%
“…Indeed, the data in Table 2 show the rates as a function of the nature of the specific metal ions added. The reasons for the metal effects are not clear, but we believe that the efficiency is partly correlated with the Lewis acidity of the metals when combining with strong ligands, such as the nitrogen on the polyethylenimine backbone or the imidazoles (14,28).…”
Section: Resultsmentioning
confidence: 99%